Предмет: Алгебра,
автор: sultanova2003
Преобразуйте в многочлен стандартного вида а) (2y-3)(2y+3)
Б) (x-7)^2-3x(x-5)
Ответы
Автор ответа:
0
a) (2y-3)(2y+3) =
2y*2y + 3*2y -3*2y + 3*3 =
4*(y^2) + 9
б) (x-7)^2-3x(x-5) =
x^2 - 14x + 49 - 3*(x^2) + 15x =
-2*(x^2) + x + 49
2y*2y + 3*2y -3*2y + 3*3 =
4*(y^2) + 9
б) (x-7)^2-3x(x-5) =
x^2 - 14x + 49 - 3*(x^2) + 15x =
-2*(x^2) + x + 49
Похожие вопросы
Предмет: Литература,
автор: wwdenww24
Предмет: Алгебра,
автор: Аноним
Предмет: Геометрия,
автор: dashasmol2009
Предмет: История,
автор: anipac
Предмет: Алгебра,
автор: fsdfggjuymjg